Variation in human chromosome 21 ribosomal RNA genes characterized by TAR cloning and long-read sequencing - Kim, Jung-Hyun; Dilthey, Alexander T; Nagaraja, Ramaiah; Lee, Hee-Sheung; Koren, Sergey; Dudekula, Dawood; Wood III, William H; Piao, Yulan; Ogurtsov, Aleksey Y; Utani, Koichi; Noskov, Vladimir N; Shabalina, Svetlana A; et al. (Nucleic acids research, 2018)
Abstract Despite the key role of the human ribosome in protein biosynthesis, little is known about the extent of sequence variation in ribosomal DNA (rDNA) or its pre-rRNA and rRNA products. We recovered ribosomal DNA segments from a single human chromosome 21 using transformation-associated recombination (TAR) cloning in yeast. Accurate long-read sequencing of 13 isolates covering ∼0.82 Mb of the chromosome 21 rDNA complement revealed substantial variation among tandem repeat rDNA copies, several palindromic structures and potential errors in the previous reference sequence. These clones revealed 101 variant positions in the 45S transcription unit and 235 in the intergenic spacer sequence. Approximately 60% of the 45S variants were confirmed in independent whole-genome or RNA-seq data, with 47 of these further observed in mature 18S/28S rRNA sequences. TAR cloning and long-read sequencing enabled the accurate reconstruction of multiple rDNA units and a new, high-quality 44 838 bp rDNA reference sequence, which we have annotated with variants detected from chromosome 21 of a single individual. The large number of variants observed reveal heterogeneity in human rDNA, opening up the possibility of corresponding variations in ribosome dynamics.